Eating disorders sourcebook : basic consumer health information about anorexia nervosa, bulimia nervosa, binge eating, compulsive exercise, female athlete triad, and other eating disorders ... - Shannon, Joyce Brennfleck (Detroit, MI : Omnigraphics, 2007)
"Provides basic consumer health information about risk factors, recovery from, and prevention and treatment of various eating disorders. Includes index, glossary of related terms, and other resources"--Provided by publisher.
pt. VI. Additional help and information -- 68. Glossary of terms related to eating disorders -- 69. Online resources for more information about eating disorders -- 70. Additional resources for information about eating disorders.
Includes bibliographical references and index.
Keywords: Eating disorders; Consumer education